The analysis of illocutionary act in “big four movie” - Muhammad Ridho Latuapo; Wening Sahayu (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2024)
Speech acts are a part of pragmatic science that examines the meaning expressed by the speaker and involves the listener. A speech act is a statement or utterance that has the effect of action and social impact. This study aims to identify the illocutionary act performed in “Big Four” movie This research used descriptive qualitative study which reveals the data collection on the film transcript through the character’s dialogue in the film. The result of the study will be discussed are: first, the function of illocutionary act in the movie are: representative act is used to inform, prohibition, assert and claim while directive act is used to ask, warning, command, request, and suggest. Then expressive is used to thank, greeting, apologize, compliment, and commissive act is used to promise, refuse, and plan. The last, the types of illocutionary act which is frequently used by the characters in the movie is directive act.